2017
DOI: 10.1007/s12671-017-0817-8
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy Versus Pure Cognitive Behavioural Self-Help for Perfectionism: a Pilot Randomised Study

Abstract: This pilot study compared mindfulness-based cognitive therapy (MBCT) with a self-help guide based on cognitive behaviour therapy (CBT) for university students experiencing difficulties due to perfectionism. Participants were randomised to an MBCT intervention specifically tailored for perfectionism or pure CBT self-help. Questionnaires were completed at baseline, 8 weeks later (corresponding to the end of MBCT) and at 10-week follow-up. Post-intervention intention-to-treat (ITT) analyses identified that MBCT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 56 publications
(71 reference statements)
3
41
0
8
Order By: Relevance
“…It is possible that by helping youth to notice and accept their cognitions, emotions, and somatic experience without judgment, they may have learned to apply their newfound nonjudgmental frame of mind to their perfectionistic cognitions. Indeed, these results were consistent with studies that found mindfulness interventions were correlated with a decrease in perfectionism (James & Rimes, 2018). Unfortunately, there was not a large enough sample in this study to demonstrate whether increased levels of mindfulness mediated lower levels of perfectionism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is possible that by helping youth to notice and accept their cognitions, emotions, and somatic experience without judgment, they may have learned to apply their newfound nonjudgmental frame of mind to their perfectionistic cognitions. Indeed, these results were consistent with studies that found mindfulness interventions were correlated with a decrease in perfectionism (James & Rimes, 2018). Unfortunately, there was not a large enough sample in this study to demonstrate whether increased levels of mindfulness mediated lower levels of perfectionism.…”
Section: Discussionsupporting
confidence: 90%
“…Several interventions have been tried to mitigate the negative effects of perfectionism, including affective programming (Mofield & Chakraborti-Ghosh, 2010), cognitive behavior therapy (James & Rimes, 2018), and mindfulness (James & Rimes, 2018). There is growing interest in the use of mindfulness as a tool for gifted students to increase self-awareness, reframe potentially negative tendencies such as perfectionism, and improve attention to the present moment (Sharp et al, 2017).…”
mentioning
confidence: 99%
“…There was evidence that unguided self-help using CBT approach can reduce perfectionism [ 70 ]. A recent study [ 71 ] also found that the use of a CBT self-help booklet significantly improved participants’ self-compassion, although to a lesser degree compared with mindfulness-based cognitive therapy. Our findings added to this area of literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive Behaviour Therapy for perfectionism (CBT‐P) is considered to the treatment of choice as it has been found to not only produce large effect size reductions in perfectionism, but also produce moderate effect size decreases in depression and anxiety (Lloyd, Schmidt, Khondoker, & Tchanturia, ), compared to control conditions. Apart from CBT‐P, one non‐randomised examination of a group psychodynamic therapy exists (Hewitt et al, ), as does one randomised trial comparing Mindfulness‐Based Cognitive Therapy to a 50‐page self‐help booklet informed by CBT (James & Rimes, ). This latter study is hard to interpret given the confounding factors of contact with therapist and other participants in the former compared to the latter condition.…”
mentioning
confidence: 99%